KONTROL SOSIAL MASYARAKAT DALAM UPAYA MENGATASI KENAKALAN REMAJA PUTUS SEKOLAH (Studi Kasus di Desa Tanjung Una, Kec. Taliabu Utara, Kab. Pulau Taliabu) - Taufik Boda; Wahyudin Noe; Nani Rajaloa (Universitas Khairun, 2024)
This research is based on a phenomenon of juvenile delinquency dropping out of school in Tanjung Una village, North Taliabu District, which is increasingly widespread, such as cheating, drunkenness and livestock theft which has disturbed the residents. Therefore, it is important to explore the role of the community in the village in exercising social control over juvenile delinquency. This research uses a qualitative approach with a case study method. The results illustrate that the role of the community in dealing with delinquency among out-of-school teenagers in Tanjung Una village is carried out in several ways, namely: 1) reprimanding teenagers who race motorbikes and get drunk, 2) approach and give advice to out-of-school teenagers to return to school, and 3 ) resolve juvenile delinquency through deliberation involving the perpetrator, parents and the village government, but if it involves unlawful acts (for example: stealing people's livestock) then it is handled directly by the village government in the form of strict sanctions/punishments. The obstacles faced by the community in dealing with delinquency among teenagers who have dropped out of school consist of 2 (two) factors, namely internal factors such as individual teenagers who find it difficult to accept advice from parents or residents and external factors originating from the family environment which pays little attention to children's relationships, love and affection. affection, as well as disharmonious family life.